Superposição de estados comprimidos de dois modos e aplicações em informação quântica - Cardoso, Fernando Redivo (Universidade Federal de São Carlos, 2019)
In this work, we present a new class of quantum states for applications in quantum metrology and quantum information, the states here named as “Even EPR” and “Odd EPR”. We present a review of the basic concepts of quantization of the electromagnetic field, along with the probability functions and distributions in phase space. We present the main states of the electromagnetic field and their relevant statistical properties, besides the basic concepts involved in quantum metrology for a single parameter estimation. The new class of states is presented, and its general properties are discused. With a simple definition of separability for two-mode pure states, the entanglement properties between the modes of the field are studied, and its quantifications are directly compared with the original EPR states. We present results about applications of the Even and Odd EPR states in quantum metrology for estimation of a single parameter, comparing the results with the single-mode squeezed states, which has great importance in quantum metrology. Lastly, we show that acting locally onto one of the modes of the even and odd EPR states, it is possible to construct what we call “pseudo-thermal” states of the field, which consists in mixtures of Fock states previously selected through the preparation process, with probability coefficients which correspond to thermal distribution of photons.
Superposition of two-mode squeezed states and applications in quantum information
Keywords: Interação radiação-matéria; Estados do campo eletromagnético; Emaranhamento; Metrologia quântica; Informação quântica de Fisher; Estados térmicos; Radiation-matter interaction; States of the electromagnetic field; Entanglement; Quantum metrology; Quantum Fisher information; Thermal States; CIENCIAS EXATAS E DA TERRA::FISICA